The effect of trade openness on child labor: Empirical evidence from developing economies - Rossazana, Ab-Rahim; Bilal, Tariq (Universiti Putra Malaysia, 2016)
The aim of this study is to investigate the impact of international trade on the child labor by using new trade theory among the developing countries based on trade induced child labor effects. The relationship between the child labor and the selection and scale effect for the developing countries which are engaged in the trade of both differentiated and homogeneous goods is further examined. The ratio of gross domestic product (GDP) and industrial value added represents the scale effect while the selection effect refers to the exit of least efficient firms due to trade liberalization. The results of generalized least squares (GLS) technique show child labor decreases with an increase in the value added. In addition, the findings also indicate the overall effect of trade along with trade child labor induced effects is favorable in the reduction of child labor. The results imply trade liberalization is a gain to the developing economies in the form of child labor reduction.